2012
DOI: 10.1212/wnl.0b013e3182698d6c
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in rapid-onset dystonia-parkinsonism

Abstract: Objective: Rapid-onset dystonia-parkinsonism (RDP) is caused by a variety of missense mutations in the ATP1A3 gene. Psychiatric comorbidity has been reported, although systematic examination of psychiatric disease in individuals with RDP is lacking. This study examines psychiatric morbidity for 23 patients with RDP in 10 families with family member control subjects and in 3 unrelated patients with RDP, totaling 56 individuals.Methods: Twenty-nine ATP1A3 mutation-positive individuals were examined; 26 exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 20 publications
4
56
1
Order By: Relevance
“…Recent work suggests that RDP patients may exhibit an elevated prevalence of mood disorders (50%) and psychosis (19%) compared to relatives without an ATP1A3 mutation. 40 These findings were observed across families with different ATP1A3 mutations, and are consistent with reports of depression in individuals with ATP1A3 mutations causing motor problems. 16 …”
Section: Diseases Caused By Mutations In Atp1a3supporting
confidence: 89%
See 1 more Smart Citation
“…Recent work suggests that RDP patients may exhibit an elevated prevalence of mood disorders (50%) and psychosis (19%) compared to relatives without an ATP1A3 mutation. 40 These findings were observed across families with different ATP1A3 mutations, and are consistent with reports of depression in individuals with ATP1A3 mutations causing motor problems. 16 …”
Section: Diseases Caused By Mutations In Atp1a3supporting
confidence: 89%
“…14,16,19,20,40 A recently published cohort of 26 RDP patients indicated that 76% of patients had onset of motor symptoms by the age of 25. 40 In addition to dystonia, there can also be non-motor manifestations in RDP patients. Recent work suggests that RDP patients may exhibit an elevated prevalence of mood disorders (50%) and psychosis (19%) compared to relatives without an ATP1A3 mutation.…”
Section: Diseases Caused By Mutations In Atp1a3mentioning
confidence: 99%
“…Similar anatomical regions have been implicated in DYT11 cohorts with loss of inhibition thought to contribute to the motor hyperkinesis and co-morbid anxiety [36]. Monoamine involvement has also been implicated in DYT12 cohorts with altered levels detected in CSF studies and immunostaining localizing the NA/K-ATPase to the basal ganglia of mouse models [38,45]. Neuropathological studies of DYT3 cases demonstrated neuronal loss and astrocytosis in caudate and putaminal regions, with corresponding reduced neuropeptide Y labelling [46].…”
Section: Discussionmentioning
confidence: 78%
“…Targeted questionnaires found significantly elevated rates of anxiety (p ¼ 0.068) and depression (p ¼ 0.025), but no differences in OCD scores. Age at onset of the psychiatric symptoms also predated the movement disorder in ten cases, these included: mood disturbance (n ¼ 1), anxiety disorder (n ¼ 4), psychosis (n ¼ 2) and substance misuse (n ¼ 3) [38]. No evidence of psychiatric illness was identified in any of the NMC cases.…”
Section: Dyt12: Rapid-onset Dystonia Parkinsonismmentioning
confidence: 99%
“…Mood disorders and psychoses have a higher prevalence in patients with rapid onset dystonia-parkinsonism (DYT12) than in non-mutant carriers 23,24 . Psychiatric non-motor features are also found in sporadic forms of primary dystonia.…”
mentioning
confidence: 99%